(untitled) (International Journal of Engineering and Computer Science, 2016)
The solar photovoltaic has the advantage of direct conversion of sunlight to electricity and also suitable for most of the regions therefore it is highly preferred when compared to other renewable energy sources. So the PV energy is considered as the source for the voltage lift technique. Voltage lift technique is a popular method wildly used in electronic circuit design. It has been successfully employed in dc-dc converter application in recent years and opened a way to design high voltage converters. However the voltage increases stage by stage along arithmetic progression. When compared with MLI where the harmonic content deteriorate as the number of levels increases, the super-lift dc-ac converter can reduce the harmonics with reduced number of levels and reduced devices. In the proposed super-lift dc to ac inverter the output increases stage by stage